Differential Severe Acute Respiratory Syndrome Coronavirus 2 Antibody Profiles After Allergic Reactions to Messenger RNA Coronavirus Disease 2019 Vaccine . (23rd March 2022) - Maron, Jenny S; Conroy, Michelle; Naranbai, Vivek; Samarakoon, Upeka; Motazedi, Tina; Farmer, Jocelyn R; Freeman, Esther; Banerji, Aleena; Bartsch, Yannic C; Gregory, David J; Poznansky, Mark C; Alter, Galit; et al.
Abstract: Allergic symptoms after messenger RNA (mRNA) coronavirus disease 2019 (COVID-19) vaccines occur in up to 2% of recipients. Compared to nonallergic controls (n = 18), individuals with immediate allergic reactions to mRNA COVID-19 vaccines (n = 8) mounted lower immunoglobulin G1 (IgG1 ) to multiple antigenic targets in severe acute respiratory syndrome coronavirus 2 spike following vaccination, with significantly lower IgG1 to full-length spike ( P = .04). Individuals with immediate allergic reactions to mRNA COVID-19 vaccines bound Fcγ receptors similarly to nonallergic controls. Although there was a trend toward an overall reduction in opsonophagocytic function in individuals with immediate allergic reactions compared to nonallergic controls, allergic patients produced functional antibodies exhibiting a high ratio of opsonophagocytic function to IgG1 titer. Abstract : Compared to nonallergic controls (n = 18), individuals with immediate allergic reactions to mRNA COVID-19 vaccines (n = 8) mounted lower IgG1 to multiple antigenic targets in SARS-CoV-2 spike following vaccination, with significantly lower IgG1 to full-length spike ( P = .04).